1996
DOI: 10.1007/bf00438918
|View full text |Cite
|
Sign up to set email alerts
|

In vitro sensitivity of Verticillium fungicola to selected fungicides

Abstract: Twenty isolates of Verticillium fungicola var. fungicola collected from diseased fruit-bodies of Agaricus bisporus from prochloraz-treated crops, were exposed to a range of concentrations of six chemicals (benomyl, chlorothalonil, formaldehyde, iprodione, prochloraz-Mn-complex and prochloraz + carbendazim) in vitro. EC(50) values were determined for each fungus-fungicide combination. All isolates were more sensitive to prochloraz-Mn-complex (EC(50) values less than 5 mg 1(-1)) than to the remainder fungicides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Maximum percent growth inhibition was recorded in Carbendazim followed by Thiophanate-methyl, Dithane Z-78 and Dithane M-45, respectively. Our findings gets support from the reports of Sinden (1949), Hu and Dough (1965), Smith (1970), Fletcher (1971) and Gea et al (1977Gea et al ( , 2011Gea et al ( , 2012 who observed that different isolate of V. fungicola were sensitive to Prochlorage Mn complex followed by Prochlorage + Carbendazim.…”
Section: Effect Of Different Fungitoxicants On Verticillium Fungicolasupporting
confidence: 91%
“…Maximum percent growth inhibition was recorded in Carbendazim followed by Thiophanate-methyl, Dithane Z-78 and Dithane M-45, respectively. Our findings gets support from the reports of Sinden (1949), Hu and Dough (1965), Smith (1970), Fletcher (1971) and Gea et al (1977Gea et al ( , 2011Gea et al ( , 2012 who observed that different isolate of V. fungicola were sensitive to Prochlorage Mn complex followed by Prochlorage + Carbendazim.…”
Section: Effect Of Different Fungitoxicants On Verticillium Fungicolasupporting
confidence: 91%
“…[25] The isolates were considered resistant to a fungicide if its ED 50 exceeded 50.0 mg L ¡1 , weakly resistant if the ED 50 was in the range between 5.0 and 50.0 mg L ¡1 , and sensitive if the value was less than 5.0 mg L ¡1 . [26] A selectivity index for each active ingredient was calculated as a ratio of the ED 50 mean value for each tested isolate of the pathogen and a corresponding estimate for A. bisporus. [19] Statistical analyses…”
Section: Antifungal Activitymentioning
confidence: 99%
“…This observation corresponds with the report by Erickson et al 22 indicating that sensitivity to a DMI fungicide among individuals not yet exposed to such a fungicide varies from highly sensitive to more resistant phenotypes. However, in this study, no isolate had an ED 50 value of less than 5 mg/L or more than 50 mg/L to render them, respectively, moderately or highly resistant according to the criteria set by Russell et al 34 cited by Gea et al 24 The 12 isolates studied from the South African mushroom industry were highly sensitive to prochloraz manganese (ED 50 =0.0002-0.55 mg/L) and there were significant differences among the isolates under study. However, none of the isolates was resistant to prochloraz manganese.…”
Section: Discussionmentioning
confidence: 58%
“…November/December 2015 in a practical resistance once the frequency of phenotypes prevents commercially acceptable disease control levels to be achieved under standard usage regimes. 23 The fact that resistance has developed in L. fungicola 21,24 and many other pathogens of field crops, [25][26][27] combined with the fact that most Cladobotryum spp. produce abundant conidia and have repeated infection cycles, may suggest that Cladobotryum spp.…”
Section: Volume 111 | Number 11/12mentioning
confidence: 99%